Conditional freedom: repercussions in the family living with a member on peritoneal dialysis - Timm, Arlete Maria Brentano; Beuter, Margrid; Girardon-Perlini, Nara Marilene Oliveira; Pauletto, Macilene Regina; Santos, Naiana Oliveira dos; Bruinsma, Jamile Lais (Rev Rene, 2015)
Objective: to describe the repercussions in the family living with a member on peritoneal dialysis at home. Methods: qualitative research conducted in a clinic for kidney dysfunctions in southern Brazil. Interviews were conducted with seven families. The data were submitted to thematic analysis. Results: two themes emerged: demands arising from dialysis: a prison in families’ lives; and restrictions and family adjustments to treatment: the conditional freedom. It was found that the families coping with peritoneal dialysis at home lose their freedom, this being subject to treatment needs. Conclusion: living with a family member on peritoneal dialysis causes repercussions in various spheres in the families’ routine. The nurse can help in these situations, by identifying problems and proposing alternative to meet the specific needs of each family.